Atividade antimicrobiana e antioxidante de Licania rigida e Turnera ulmifolia - Morais, Leandro Vinícius Fernandes de (2015)
Introduction: Licania rigida Benth and Turnera ulmifolia Linn. var. elegans are species of semi-arid regional plants used in the treatment of various diseases. Objectives: The purpose of this study was chemically characterize the extracts and fractions and investigate the antimicrobial and antioxidant potential. Methods: For chemical analysis, were performed spectrophotometric quantification of the total phenolic and characterization of the extracts by chromatographic analysis. Evaluation of antioxidant activity was done by determining the radical scavenging capacity DPPH •. Antimicrobial activity was evaluated by agar diffusion, broth microdilutionand time-kill assays. Results: The extracts and fractions L. rigid and T. ulmifolia showed a high phenolic content, the presence of flavonoids, which were determined as chemical markers. It was observed that the extracts of both species performed as sequestering agents in the trial of antioxidant activity in vitro. The L. rigida extract was the only active front strains of S. aureus 33591 (methicillin-resistant), S. aureus 29213, S. epidermidis 12228, and also against the yeast, Candida albicans, Candida dubliniensis, Candida tropicalis, Candida parapsilosis, Candida rugosa, Candida krusei eTrichosporon asahii. Conclusions: Based on these results it is possibly affirm the antioxidant and antimicrobial activity of L. rigida and attributed the presence of polyphenolic flavonoid like responsible.